BASIC KNOWLEDGE OF SOFTWARE AND WEB CONTENT AS ELEMENTS OF SOCIAL PROGRAMMING IN EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
For any specialist, basic knowledge of his or her specialty is like a "daily routine" that should create comfortable conditions for the realization of basic professional tasks. At the same time, the changes brought about by the transition to a remote format of communication, professional activity and the need to use the mechanisms of the information society affect the basic process of socialization, formation and development of personality. This process is part of the educational process - the "knowledge acquisition routine" or social programming that meets the needs of the state, society, national culture, etc. And it cannot have primary and/or secondary aspects.That is why the task of our research on this topic is to try to figure out what basic knowledge of software and web content, including programming skills, can be the necessary minimum in teacher training for everyday activities in the digital world (including the needs of society and the interests of children/youth). What should be a prerequisite for quality interaction between teachers, subjects and objects of the educational process in the digital world. In particular, what format, ethical norms and legislative aspects of regulation of the digital educational process, including relevant content, should be the basis for such interaction.